A marketing térhódítása a hazai felsőoktatásban - Rámháp, Szabolcs (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Demographical changes and reforms in the higher education in the last years change the state of the educational system at Hungary. It’s started a sharp competition between each university for applicants, and so indirectly for survival. Universities, which lose on this competition, require closing their institutions, making layoff, or have to be merged into another university. In like competitive situation the importance of marketing is sharply rising. Higher educational institutions should give up their privileged position, and have to apply consciously and efficiently the instruments of marketing. They apply like way of marketing and communication, which were previously by business sector used. There is a lot of applicable element, but the challenge for these very special institutions is compli-cated.